ChemInform Abstract: Application of Design of Experiments (DoE) Optimization to the One‐Pot Synthesis of 4, 6‐Dihydropteridinones. Issue 7 (January 2016) - Stone, Steven; Wang, Tiansheng; Liang, Jianglin; Cochran, John; Green, Jeremy; Gu, Wenxin
Abstract: A one‐pot procedure to synthesize title compounds such as (III), (V), (VII), and (IX) from pyrimidines (I) and amino acid derivatives is studied and the reaction parameters are optimized.